Kebijakan Penyedia Infrastruktur Irigasi Pada Program Swasembada Beras di Desa Tura Kecamatan Pulau Malan Kabupaten Katingan - Mambang Mambang; Pebry Agusthen (Pencerah Publik, 2019)
Katingan Regency as one of the regencies in Central Kalimantan province that has potential agricultural land potentials should implement the policy of agricultural irrigation infrastructure in the village of Tura District Malan Island District Katingan. Therefore, in this research researchers want to see the factors that cause the irrigation infrastructure to be inadequate. The type of research used is qualitative research with the techniques of data collection interviews, observations, documentation, tape recorders. The results of this study describe the infrastructure of irrigation channels, which means and infrastructures have not been adequate. Irrigation channels in irrigating farmland farmers have already had irrigation channels that will always channel the water source. The problem of irrigation channels today is the absence of water doors on the irrigation channels in the village of Tura so that water often comes out in the rainy season so that from the irrigation channels in the dry season, there is often drought in water due to lack Water availability for paddy fields in the village of Tura, it is reaping complaints from the farmers in question because it greatly affects the crops of the farmers, facilities and infrastructure of the irrigation tract system is insufficient so that the harvest obtained only 2-3 Per year until the harvest each day only for the daily needs of farmers in the village of Tura, but the provider of irrigation infrastructure has not been adequate in the village of Tura because of the budget cuts in the agricultural service by the local government for the opening Road access.